Pengaruh Partisipasi Anggaran dan Gaya Kepemimpinan Terhadap Kinerja Manajerial dengan Job Relevant Information sebagai Pemoderasi - Syukri, Muhammad; Surasni, Ni Ketut; Furkan, Lalu M. (E-Jurnal Akuntansi; Vol 29 No 3 (2019)DO - 10.24843/EJA.2019.v29.i03.p06, 2019)
The study aims to reveal the effect of budgetary participation and leadership style on managerial performance as well as the influence of job relevant information in strengthening the influence of budgetary participation relationships and leadership style on managerial performance. Sources of data in the study using a questionnaire distributed to 43 West Lombok Regency OPD. The results showed budget participation and leadership style involved managerial performance and the original sample value showed positive budget participation and leadership style related to the direction of managerial performance, work related information did not support job relevant information did not support improvement of leadership style on managerial performance and sample value Original shows negative. Keywords : Budgetary Participation; Leadership Style; Job Relevant Information Managerial Performance.